Comparative voltammetric determination of ascorbic acid at three different carbon electrodes: application of carbon screen-printed electrode for citrus fruits analysis - Paina, Talytha Rodrigues Gaspari; Eleotério, Izabel Cristina; Stradiotto, Nelson Ramos [UNESP]; de Oliveira, Marcelo Firmino (International Association of Physical Chemists (IAPC), 2025)
Determining the vitamin C (ascorbic acid) content in citrus fruits is crucial for dietary and nutritional considerations. Traditional analytical methods for ascorbic acid analysis often involve expensive and less portable electrodes, limiting their practicality in food analysis. This study focuses on the quantification of ascorbic acid in citrus fruits using a cost-effective and portable carbon screen-printed electrode. The efficiency of these electrodes was assessed using cyclic voltammetry and linear sweep voltammetry due to the irreversible oxidation behavior of ascorbic acid. A comparative analysis was performed with glassy carbon, carbon paste, and commercial carbon screen-printed electrodes, focusing on sensitivity variations based on analyte concentration and scanning rate. The carbon screen-printed electrode demonstrated superior sensitivity to the other electrodes tested, establishing it as a practical alternative for ascorbic acid analysis in citrus fruits. This study employed the standard addition method in conjunction with linear sweep voltammetry to accurately determine ascorbic acid concentrations in pear-orange, Tahiti lemon, and Ponkan tangerine samples. The obtained values were cross-referenced with existing literature data, enhancing our understanding of vitamin C content in these citrus fruits. Overall, this research highlights the potential of the carbon screen-printed electrode as a valuable tool for vitamin C analysis, offering new insights into food science and nutrition.
Keywords: carbon electrodes; juice samples; standard addition method; Vitamin C; voltammetry techniques